Effectiveness of Bay Leaf Extract (Syzygium polyanthum) on Uric Acid and Cholesterol Levels in Caffeine-Induced Male Mice (Mus musculus) - Pratama, Fahrul Andika; Aisyafalah, Salma; Kurnijasanti, Rochmah (Journal of Basic Medical Veterinary, 2024)
Bay leaf (Syzygium polyanthum) is one of the plants from Indonesia that has the potential to be used as a raw material for herbal medicine. Pharmacologically, bay leaves containing flavonoids have been shown to have antioxidant activity, which can reduce hyperuricemia and blood cholesterol levels. This study aims to determine the effectiveness of bay leaf extract in reducing uric acid and cholesterol levels in the blood of mice induced by caffeine. The mice tested animals were divided into six groups, namely a positive control group of uric acid, a positive control of cholesterol, where a positive control of uric acid was given allopurinol and a positive control of cholesterol was given simvastatin, a negative control was given Na-CMC 1%, and a group that was given bay leaf extract in different dose levels, namely P1 was given 20 mg/kg BB, P2 was given 40 mg/kg BB, and P3 was given 80 mg/kg BB. The parameters used were the decrease in blood uric acid and cholesterol levels caused after the treatment was measured using a POCT strip test for uric acid and cholesterol. The data obtained were statistically processed using the One-Way Anova test. The results of the Anova test showed a significant difference (p<0.05) in the data on uric acid and cholesterol levels. Then continued with the results of Duncan's test to see the most effective dose level for bay leaf extract in reducing uric acid and cholesterol levels. In Duncan's test results, it was found that the P3 group of mice with a dose of 80 mg/kg BB was the most effective dose level in reducing uric acid and cholesterol levels in the blood of mice induced by caffeine.